Literature Review & Qualitative Study: Contextual Teaching Materials for Elementary School Students’ Understanding of Fractions - Siti Nur Millah (MIREJ: Multidisciplinary Innovation Research Journal, 2025)
This research employs a framework derived from rapid technological advances, which demand innovation and creativity in the learning process in the classroom so that the material presented is relevant and effective for students. Teachers are required to develop learning media that can support students' understanding optimally, one of which is through the use of textbooks as the main source of knowledge. This study used descriptive qualitative method with data collection through interviews, documentation, and literature review to examine the effectiveness of mathematics textbooks in fraction materials. Data analysis was conducted to understand the extent to which the textbook can help students understand the concept of fractions comprehensively. The results showed that the use of fraction-based math textbooks was considered appropriate and effective by both teachers and students in the classroom. Therefore, this textbook can serve as an alternative learning media that supports the improvement of students' understanding, especially in the subject of fractions, thus improving the learning process more effectively and efficiently.